(untitled) (Web of Teachers: Inderscience Research, 2025)
This study investigates the learning experiences of beginner-level students of Russian as a foreign language (RFL) from Uzbek and Indian (English-speaking) backgrounds. Based on survey responses from 45 participants, the research explores key motivations, difficulties, preferred learning methods, and use of digital tools. The results reveal that while grammar is the most common challenge for both groups, learning preferences differ: Uzbek students benefit more from speaking and interaction, while Indian learners rely more on English-based support and structured digital tools. The findings provide insights into improving RFL instruction in multicultural classrooms.